An insight into Clostridium difficile infection: a single-center retrospective case-control study - Haddad, Fady G.; Zaidan, Julie; Polavarapu, Abhishek; Khan, Hafiz; Khan, Asif; Mudduluru, Bindu Madhavi; Saabiye, Joseph; Lukanovic, Slobodanka; Demissie, Seleshi; Mulrooney, Stephen; Khalil, Ambreen (Zeitschrift für Gastroenterologie, 2019)
Background Clostridium difficile infection (CDI) has become a worldwide health problem in view of its significant incidence and medical and economic impact on the health system. Prior studies have been undergone about risk factors and disease characteristics. We wanted to study the characteristics, prognostic factors associated with CDI at our institute, as well as a new prognostic factor.Methods Our study aimed at describing the risk factors, patient characteristics, and outcomes associated with healthcare facility–acquired CDI (HCFA-CDI) and community-acquired CDI (CA-CDI). We intended to identify the factors associated with worse outcomes. We evaluated the characteristics associated with CDI over 3 years. We also evaluated a simple neutrophil-lymphocyte ratio (NLR) and its predictive value for worse outcomes.Results Six hundred patients were enrolled (333 in a control group; 171 in the HCFA-CDI group and 96 in the CA-CDI group). NLR > 5 predicted increased mortality and intensive care unit transfer in all CDI if done as early as day 2 after CDI diagnosis. In HCFA-CDI, NLR > 5 predicted a higher ICU transfer if done as early as day 1 post-diagnosis and with increased mortality as early as day 2 post-diagnosis. In CA-CDI, NLR > 5 predicted a higher mortality and ICU transfer if done at least 4 days after diagnosis. Moreover, every 10-unit increase in NLR was associated with a significant increase in mortality and ICU transfer in patients with CDI.Conclusion A timely use of NLR can be used as a mean to predict worse outcomes, namely ICU transfer and mortality, in patients with CDI.
Keywords: Clostridium difficile; healthcare-associated diarrhea; nosocomial diarrhea